Micropropagation of Handroanthus heptaphyllus (Vell.) Mattos from seedling explants - Duarte, Evelyn Raquel (2016)
Handroanthus heptaphyllus (Vell.) Mattos (Bignoniaceae), a tropical forest tree, is a source of wood suitable for the manufacture of fine furniture and chemical compounds with medicinal and insecticidalproperties. Poor seed viability of this species limits the conventional propagation practice. In vitro germination of seeds was achieved in semi-solid Murashige and Skoog?s (MS) medium. A disinfectionprotocol was optimized for germination and growth of seedlings in vitro. Proliferation of shoots from cotyledonary and stem nodal segments was achieved in semi-solid MS medium supplemented with 22.2 μM 6-benzyladenine. Temporary immersion culture promoted elongation and rooting of shoots andreduced the shoot tip necrosis compared with culture on semisolid medium (6.7±2.7 and 41.7±7.0%,respectively; P = 0.001). Plantlets derived from temporary immersion showed better performance during the acclimatization phase. This is the first report on micropropagation of H. heptaphyllus.